The genus Pyroderces Herrich-Schäffer new to China, with description of a new species (Lepidoptera, Cosmopterigidae) - Zhang, Zhiwei; Li, Houhun (Zootaxa, 2009)
The genus Pyroderces Herrich-Schäffer is recorded for the first time from China. Three species are included: Pyroderces bifurcata sp. nov. is described as new; P. argyrogrammos (Zeller) and P. sarcogypsa (Meyrick) are newly recorded for China. Images of the adults and the genitalia are provided, along with a key to the species from China.